Social Entrepreneurship Orientation, Organizational Commitment, and Ambidextrous Leadership: Enhancing Village-Owned Enterprises Performance - Azhari, Intan Putri; Nofirda, Fitri Ayu; Junita, Dewi (Universitas Brawijaya, Indonesia, 2025)
Studies on performance-improving techniques are called for as Village-Owned Enterprises (BUMDesa) in Indonesia demonstrate poor performance; 1,094 of 1,601 BUMDesa in Riau Province function at basic levels, and only 195 attain advanced classification. This study presents an integrated mediation-moderation model examining how social entrepreneurship strategy affects BUMDesa performance through organizational commitment mediation, moderated by ambidextrous leadership. Data were obtained from BUMDesa directors and were analyzed using quantitative SEM-PLS analysis. Results reveal that although organizational commitment has a favorable influence and serves as a partial mediator, the social entrepreneurship method also has a clear influence on organizational commitment and performance. But ambidextrous leadership shows no meaningful moderating effect. This paper presents the first empirical investigation of an integrated mediation-moderation model in Indonesian village companies, therefore extending the Resource-Based View theory to rural environments. Results guide policymakers' decisions on capacity-building programs for sustainable rural economic development through social entrepreneurship development, thereby providing strategic frameworks for strengthening organizational commitment.